Ultrastructural studies distinguish skin diversities among Galápagos iguanas - Manuel Scimeca; Rita Bonfiglio; Giuliano Colosimo; Eleonora Candi; Glenn P. Gerber; Gregory A. Lewbart; Alessandro Mauriello; Gerry Melino; Christian Sevilla; Yufang Shi; Ying Wang; Gabriele Gentile (Biology Direct)
Abstract Iguanas exhibit diverse colors and behaviors reflecting evolutionarily adaptation to various habitats; in particular, the Galápagos iguanas represent unique color morphologies with distinct ecological niches. While external coloration in iguanas has ecological implications, comprehensive studies on the histological and ultrastructural aspects of their skin can provide insight into their adaptation to extreme environments, such as high UV exposure. Starting from these considerations the present study investigates the histological, ultrastructural and immunohistochemical features to comprehensively characterize the skin in adults of three species of Galápagos iguanas (A. cristatus, C. subcristatus and C. marthae). Morphological analysis revealed significant differences among the species, with the black-colored skin of A. cristatus showing a melanin-rich but vessel-poor dermis, while C. subcristatus and C. marthae displayed varying distributions of melanosomes and melanocytes. Notably, the absence of iridophores was consistent across all samples due to the absence of birefringent material under the optical microscope. Morphometric evaluations highlighted interspecific differences in the stratum corneum thickness, particularly between black- and non-black-colored (irrespectively if yellowish or pink) skin. The ultrastructural investigation confirmed the absence of iridophores in all analyzed samples. The cytokeratin expression assessed by immunohistochemistry showed stratified epithelium in the epidermis of C. marthae non-black-colored (pink) skin. The presence of a thickened stratum corneum and the stratification of the epidermis in non-pigmented skin could help the pink iguana to cope with the extreme conditions of the Wolf volcano, especially in relation to UV exposure. These skin characteristics may reduce the penetration power of UV rays into the superficial loose dermis, thereby attenuating potential UV-related damage such as DNA breaks and ROS generation. These findings offer insights into the adaptive strategies of these iguanas.